ECONOMIC BENEFITS OF ORGANIC VEGETABLE PRODUCTION AMONG SELECTED ORGANIC FARMS IN BUKIDNON - Joemar Dayham Javier; Maria Pia M Sison (Socio-Economics/Agribusiness Department, 2023)
This study assessed the economic benefits of organic vegetable farm production in terms of income from farm produce and farm production expenses. Three municipalities were covered in the province of Bukidnon: Lantapan, Malaybalay, and Manolo Fortich. Cost and return were used in the analysis of data. Results revealed that the economic returns in organic vegetable production are promising. Lettuce and herbs registered the highest return on investment among the organic vegetable grown in Bukidnon. A peso invested in lettuce production, farmers earned PhP 2.15 for large farms, PhP 1.35 for medium farms, and PhP 1.39 for small farms, respectively. On the other hand, small farm organic growers received a PhP 1.02 per peso of investment, while large farms received a PhP 1.27 per peso, or a 127% return on investment in organic herbs production. However, some of the organic vegetables grown by the respondents recorded a lower return on investment. For instance, a peso invested in organic cucumber production generated a net gain of only PhP 0.59 or ROI of 59% for small farms, PhP 0.38 or ROI of 38% for medium farms, and PhP 0.48 or ROI of 48% for large farms. This is because of the lower product yield per hectare.